The Solution of Modern Issues Regarding Zakat of Dinar and Dirham (Based on Sources of Fiqh of Movarounnahr) - Tukhtasinov Ruzimukhammad (Zien Journals, 2024)
In this article, the approaches of today's scholars and solutions to modern issues are discussed in the sources of Movarounnahr jurisprudence regarding the issues related to the zakat of precious stones. Also, the ratio of gold and silver, how to measure it with today's modern measurements, how to calculate the zakat of cash and commercial goods were scientifically analyzed. From the advent of Islam to the 7th century A.H., the jurists' approach to the issue also changed depending on the changes in the trade of precious stones. In the fiqh sources of Movarounnahr, gold and silver saman - cash, and precious stones such as rubies, sapphires, emeralds, turquoise, pearls - are defined as musman - goods. Also, there are types of trade such as selling goods for goods (comparison), money for money (sarf), goods for money (bay), money for goods (salam), and trade rulings of mines differ from each other. In the sources, special emphasis is placed on the consumption part of these four types of minerals. Because the relation of this trade to riba is very strong. In order for the transaction to be free of riba in consumer trade, the amount of the exchanged money should be equal if it is of the same type, but not necessarily equal if it is of a different type, but the agreement should be in cash. These issues are considered important in the application of cash and commodity transactions to Sharia today.
Keywords: problema zakyata v istochnikakh fikkha Movarunnakhr; gold and silver zakyat; dinar